Transparent mobility in IPv6 mobile: an experience report - Kohn, Rodolfo (2005)
The publication of Mobile IPv6 RFC 3775 by the IETF is a breakthrough in the data communications industry to achieve the technology convergence required by ubiquitous mobile devices. MIPv6 not only brings the possibility of innovative distributed applications and services for mobile devices but also allows a transparent use of existing distributed applications even when they have been designed and developed for non-mobile platforms. This work document describes the experience gained by testing a chat application for IPv6 [3], designed and developed for a desktop computer, on a mobile device running Mobile IPv6. The description is focused on the fundamentals of the transparent mobility property: during the tests, the device was moving from one network to a different one without affecting the applications’ TCP connections.